2019
DOI: 10.1016/j.ebiom.2019.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived astrocytes from ALS patients with mutated C9ORF72 show increased oxidative stress and neurotoxicity

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects motor neurons (MNs). It was shown that human astrocytes with mutations in genes associated with ALS, like C9orf72 (C9) or SOD1, reduce survival of MNs. Astrocyte toxicity may be related to their dysfunction or the release of neurotoxic factors.MethodsWe used human induced pluripotent stem cell-derived astrocytes from ALS patients carrying C9orf72 mutations and non-affected donors. We utilized these cells to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 55 publications
10
125
0
Order By: Relevance
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 71%
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, SOD1 and TDP-43 were dispensable in this process, and death was triggered by soluble toxic factors. Another report showed that induced pluripotent stem cell-derived astrocytes from C9orf72 patients exerted motoneuron toxicity that correlated with elevated astrocytic oxidative stress, reduced antioxidant capacity and senescence ( Birger et al , 2019 ). Interestingly, both necroptosis and oxidative stress have a potential to boost an inflammatory response, which can further increase astrocytic neurotoxicity.…”
Section: Glial Cells As Key Contributors To Als Pathogenesismentioning
confidence: 99%
“…Although there is an argument whether hyper‐ or hypoexcitability participates in the pathology of ALS, it is obvious that electrophysiological variations contain a minimal phenotype in ALS models (Hawrot et al, 2020). Recently, Ustyantseva et al (2020) generated an iPSC line from PBMC of the patient with SOD1 Asp90Ala mutation utilizing episomal vectors, and Birger et al (2019) obtained iPSC‐derived astrocytes from ALS patients with C9orf72 mutations. Birger et al found that a reduction in the secretion of various antioxidant proteins in MNs due to soluble factors secreted by C9‐mutated astrocytes played a key role in MNs apoptosis in ALA patients.…”
Section: Neurodegenerative Disease Modeling Using Ipscsmentioning
confidence: 99%
“…The results show that oxidative stress resulting from any impairment in C9‐astrocytes has a toxic effect on MNs that possibly leads to neurodegeneration. Importantly, the findings show that therapeutic approaches in familial ALS in addition to MNs can target astrocytes to decrease nervous system damage (Birger et al, 2019). In another study, Bursch et al (2019) showed that iPSC‐derived MNs from ALS patients carrying a mutation in C9orf72, SOD1, and TDP43 demonstrate some mutation‐specific modifications in glutamate receptor features in combination with calcium dynamics, supporting ALS pathogenesis.…”
Section: Neurodegenerative Disease Modeling Using Ipscsmentioning
confidence: 99%